DIPG-75. INTERSECTION OF EPIGENETICS AND IMMUNITY IN DIPG. Issue 2 (22nd June 2018) - Martin, Allison; Bell, Robert; Eberhart, Charles; Raabe, Eric; Koldobskiy, Michael
Abstract: Improved therapy for DIPG represents an urgent unmet clinical need. No meaningful improvement has been made in over 30 years, with palliative radiation leading to a median survival of just 1 year. Immune checkpoint inhibitors are an important new therapeutic modality, showing success in many adult cancers. Recently, immune checkpoint inhibitors targeting the PD-1 pathway were trialed in patients with DIPG with mixed preliminary results. The discovery that >80% of DIPGs harbor the H3K27M mutation leading to global loss of the repressive histone H3K27 trimethylation mark and DNA hypomethylation, has generated great interest in the use epigenetic modifying agents for therapy of DIPG. Hypomethylating drugs such as 5-azacytidine are well known to increase immune responsive elements in cancer cells, leading to expression of endogenous retroviral elements, neoantigens, and altered expression of major histocompatibility complexes and interferon response elements. We hypothesized that genome-wide DNA hypomethylation consequent to the H3K27M mutation may make DIPG cells more susceptible to immune modulation by hypomethylating agents. In this study we evaluated the expression of the PD-1 ligand, PD-L1, in human autopsy samples and DIPG human neurosphere cell lines. We find that in vitro, DIPG expresses PD-L1 and other immune molecules in response to epigenetic modifier drugs and interferons. Interestingly, we also find that DIPG human autopsy samples express PD-L1 primarily on infiltrating immune cells rather than tumor cells. These results highlight the complex relationship between the epigenetic state and immunogenicity of DIPG, and suggest the possibility of successful combination therapies in the future.